Environmental Factors and Leprosy in Mother and Child: A Study in Endemic Areas in East Java, Indonesia - Flora Ramona Sigit Prakoeswa; Hardyanto Soebono; Dominicus Husada; Hari Basuki Notobroto; Muhammad Yulianto Listiawan; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Leprosy is a chronic infection caused by Mycobacterium leprae. In endemic locations,children become vulnerable as a result of being continuously exposed to foci of active transmission from avery young age, especially from their mothers. This study aims to find association between environmentalrisk factors and leprosy in mothers and children in endemic areas.Methods: This study is a case-control study in endemic areas in Tuban Regency, East Java Province,Indonesia. Retrieval of data was done using structured questionnaire and direct measurement. Chi-squarewas used to assess the association between environmental factors and leprosy in mothers and children groups.Results: 22 pairs of cases and 57 pairs of controls were examined. It is found that access to clean wateris associated with leprosy in mothers in endemic areas (p value = 0.047, OR 3.080, CI 95% 2.232-4.251).Environmental factors are not associated with pediatric leprosy in endemic areas.Conclusion: The results of our study show that environmental factors are not associated with pediatricleprosy in endemic areas. Access to clean water is associated with leprosy in mothers in endemic areas.